IMPROVING MANAGEMENT EFFICIENCY IN SEWING AND KNITTING ENTERPRISES - Mamatraimov Islam Mamanazarovich (International Journal of Literature and Language Studies, 2026)
This article comprehensively analyzes the issues of effective management of human capital in sewing and knitting enterprises and increasing labor productivity through employee motivation. Within the framework of the study, tangible and intangible mechanisms of employee motivation, their impact on production efficiency, and modern management approaches used in the sewing and knitting industry were studied on a scientific basis. Also, the dynamics of development of the sewing and knitting industry of Uzbekistan, export potential and employment level were assessed based on statistical data. The results of the study show that effective motivation of employees, development of their professional competencies, and creation of favorable working conditions are important factors in increasing production efficiency and strengthening the competitiveness of enterprises.